Accuracy of a Robotic Endoscopic System in Cadaver Models with Simulated Tumor Targets: ACCESS Study - Chen, Alexander C. (Respiration, 2020)
BACKGROUND: Bronchoscopy for the diagnosis of peripheral pulmonary lesions continues to present clinical challenges, despite increasing experience using newer guided techniques. Robotic bronchoscopic platforms have been developed to potentially improve diagnostic yields. Previous studies in cadaver models have demonstrated increased reach into the lung periphery using robotic systems compared to similarly sized conventional bronchoscopes, although the clinical impact of additional reach is unclear. OBJECTIVES: This study was performed to evaluate the performance of a robotic bronchoscopic system's ability to reach and access artificial tumor targets simulating peripheral nodules in human cadaveric lungs. METHODS: Artificial tumor targets sized 10–30 mm in axial diameter were implanted into 8 human cadavers. CT scans were performed prior to procedures and all cadavers were intubated and mechanically ventilated. Electromagnetic navigation, radial probe endobronchial ultrasound, and fluoroscopy were used for all procedures. Robotic-assisted bronchoscopy was performed on each cadaver by an individual bronchoscopist to localize and biopsy peripheral lesions. RESULTS: Sixty-seven nodules were evaluated in 8 cadavers. The mean nodule size was 20.4 mm. The overall diagnostic yield was 65/67 (97%) and there was no statistical difference in diagnostic yield for lesions <20 mm compared with lesions measuring 21–30 mm, the presence of a concentric or eccentric radial ultrasound image, or relative distance from the pleura. CONCLUSIONS: The robotic bronchoscopic system was successful at biopsying 97% of peripheral pulmonary lesions 10–30 mm in size in human cadavers. These findings support further exploration of this technology in prospective clinical trials in live human subjects.